Five-Year Results of Aortic Remodeling for Acute, Subacute, and Chronic Type B Aortic Dissection Following Endovascular Repair - Yang, Guangmin; Ge, Hongwei; Wu, Guangyan; Zhang, Yepeng; Zhang, Leiyang; Zhang, Ming; Li, Xiaoqiang; Zhou, Min (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND: This study was performed to compare aortic remodeling and clinical outcomes in patients with acute, subacute, and chronic type B aortic dissection (TBAD) after thoracic endovascular aortic repair (TEVAR). METHODS: We retrospectively examined 323 consecutive patients with acute (n = 129), subacute (n = 161), and chronic (n = 33) TBAD who underwent TEVAR from June 2013 to December 2016 in in multicenter institution. Patient demographics, clinical data, and imaging characteristics were recorded and compared among the three groups. RESULTS: The three groups had comparable baseline characteristics. Perioperative mortality rates were similar among the acute (2.3%), subacute (0.0%), and chronic (0.0%) groups (P=0.34). Perioperative morbidity rates, including the rates of visceral and lower limb malperfusion and cerebral infraction, were also similar. The rate of perioperative endoleak was significantly higher in the chronic group (18.1%) than in the acute (3.9%) and subacute (3.7%) groups (P = 0.02). The mean follow-up duration was 78 ± 22 months (range, 36–101 months). The mortality rates were comparable among the three groups. The rates of reintervention and lower limb malperfusion were higher in the chronic group than in the acute and subacute groups. TL and FL diameter reduction were more robust in the acute and subacute groups than in the chronic group. CONCLUSIONS: Patients with acute, subacute, and chronic TBAD had different outcomes in this study. Patients with acute and subacute TBAD had fewer complications than those with chronic TBAD. Aortic remodeling after TEVAR was more favorable in patients with acute and subacute TBAD than in patients with chronic TBAD. TEVAR promotes more positive remodeling at the stent graft level than at the distal level of the aorta.